Termiticide activities of wood extractives of Ziziphus mauritiana (Rhamnaceae) against subterranean termites under field conditions - Zulfiqar,Sumer (2020)
Abstract Synthetic wood preservatives are the causes of large-scale environmental pollution and few have been withdrawn from the commercial markets in the past years. The present studies focused on determination of naturally present extractives of Ziziphus mauritiana as less toxic wood protectant against subterranean termites. Firstly, natural resistance of Z. mauritiana heartwood against termite was determined by exposing stakes in the field. For the preparation of extractives, air-dried Z. mauritiana heartwood and bark shavings were soaked in 1 liter each of ethyl acetate, hexane, petroleum ether and water in a bottle separately. Different dipping treatment times (36 and 72 hours) at 10, 20 and 30% concentrations of extractives on Populus deltoides wooden stakes were used and stakes were exposed to termites in submerged manner. Combination of extractives in different solvents were included as separate experiment and finally, seasoning prior to extractives application on P. deltoides wooden stakes was also done and stakes were arranged in three replications for each treatment. Maximum mean percent weight loss (81.1%) was observed in case of P. deltoides followed by boiled Z. mauritiana (15.24%) in termite resistance test. Stakes treated with petroleum ether extracts had minimum weight loss alone or in combination with other extract’s solvent in all experiments. Extractives in other solvents followed petroleum ether non-significantly but were significantly different from their respective control treatment, which had the highest weight loss (>60%). Transferring durability using extracts of Z. mauritiana increased resistance of non-durable P. deltoides against termites and extractives could be used as wood preservatives.